A Robust Intrinsically Green Fluorescent Poly(Amidoamine) Dendrimer for Imaging and Traceable Central Nervous System Delivery in Zebrafish. Issue 39 (2nd September 2020) - Wang, Guoying; Zhao, Xiaowei; Wu, Haigang; Lovejoy, David B.; Zheng, Meng; Lee, Albert; Fu, Libing; Miao, Kaiting; An, Yi; Sayyadi, Nima; Ding, Kunjie; Chung, Roger S.; et al.
Abstract: Intrinsically fluorescent poly(amidoamine) dendrimers (IF‐PAMAM) are an emerging class of versatile nanoplatforms for in vitro tracking and bio‐imaging. However, limited tissue penetration of their fluorescence and interference due to auto‐fluorescence arising from biological tissues limit its application in vivo. Herein, a green IF‐PAMAM (FGP) dendrimer is reported and its biocompatibility, circulation, biodistribution and potential role for traceable central nervous system (CNS)‐targeted delivery in zebrafish is evaluated, exploring various routes of administration. Key features of FGP include visible light excitation (488 nm), high fluorescence signal intensity, superior photostability and low interference from tissue auto‐fluorescence. After intravenous injection, FGP shows excellent imaging and tracking performance in zebrafish. Further conjugating FGP with transferrin (FGP‐Tf) significantly increases its penetration through the blood–brain barrier (BBB) and prolongs its circulation in the blood stream. When administering through local intratissue microinjection, including intracranial and intrathecal injection in zebrafish, both FGP and FGP‐Tf exhibit excellent tissue diffusion and effective cellular uptake in the brain and spinal cord, respectively. This makes FGP/FGP‐Tf attractive for in vivo tracing when transporting to the CNS is desired. The work addresses some of the major shortcomings in IF‐PAMAM and provides a promising application of these probes in the development of drug delivery in the CNS. Abstract : Intrinsically green fluorescent poly(amidoamine) dendrimer is readily prepared from surface modification of PAMAM (G5) with acetaldehyde, followed by PEGylation (FGP) and transferrin functionalization (FGP‐Tf). The developed FGP/FGP‐Tf shows excellent in vivo imaging characters in zebrafish. This study provides the rationale to examine the potential of these nanoprobes for traceable central nervous system targeted drug delivery in zebrafish.